The use of aripiprazole in early onset schizophrenia: safety and efficacy - Ibrahim, Normala; Awang, Hamidin (Malaysian Medical Association, 2009)

(untitled)
The use of atypical antipsychotic agents in early onset schizophrenia is rising despite its limited data on efficacy, safety and tolerability. Early onset schizophrenia warrants effective pharmacological treatment that is safe and well tolerated by children and adolescent population. Existing atypical agents are not completely free of side effects. Aripiprazole has unique properties that differ from other atypical antipsychotics and fill up the missing gaps, as it is associated with minimal metabolic complications and extrapyramidal side effects that are more commonly seen in other atypical agents. It offers a better option for this population and may possibly be considered as first line treatment in future. This case report demonstrates the efficacy and safety of Aripiprazole in children and adolescent population.